2018
DOI: 10.1186/s13256-018-1725-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningeal melanocytoma diagnosed using an interdisciplinary approach: a case report and review of the literature

Abstract: BackgroundMeningeal melanocytoma is a rare pigmented tumor arising from leptomeningeal melanocytes. Patients with this tumor might initially consult a dentist because a mass lesion in Meckel’s cave could manifest as dental pain and malocclusion, thereby mimicking temporomandibular disorder. The diagnostic approach, especially using imaging modalities, would be challenging in such cases unless an interdisciplinary approach is used.Case presentationHere, we report a case of a 39-year-old Japanese man who had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…[ 11 ] Due to a limited number of cases, it is difficult to calculate the incidence of such tumors. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 11 ] Due to a limited number of cases, it is difficult to calculate the incidence of such tumors. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms that lead patients to consult a doctor can be extremely different, depending on the tumor location. [ 4 ] In their study, Keng-Liang et al reported 12 patients with meningeal melanocytoma and Nevus of Ota [ 12 ] thus every patient should have a complete dermatology examination. In the case of our patient, he was Nevus of Ota-free.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations